Experimental observation of dramatic differences in the dynamic response of Newtonian and Maxwellian fluids. - Castrejón-Pita, JR; del Río, J; Castrejón-Pita, A; Huelsz, G (2003)
An experimental study of the dynamic response of a Newtonian fluid and a Maxwellian fluid under an oscillating pressure gradient is presented. Laser Doppler anemometry is used in order to determine the velocity of the fluid inside a cylindrical tube. In the case of the Newtonian fluid, the dissipative nature is observed. In the dynamic response of the Maxwellian fluid an enhancement at the frequencies predicted by theory is observed.